Nash implementation in an allocation problem with single-dipped preferences - Ahmed Doghmi (Games, 2013)
In this paper, we study the Nash implementation in an allocation problem with single-dipped preferences. We show that, with at least three agents, Maskin monotonicity is necessary and sufficient for implementation. We examine the implementability of various social choice correspondences (SCCs) in this environment, and prove that some well-known SCCs are Maskin monotonic ( but they do not satisfy no-veto power) and hence Nash implementable.
Keywords: C72; D71; 330; Nash implementation; allocation problem; single-dipped preferences